Early Grade Educators' Perception and its Influential Factors in Implementing Inclusive Education in the Akuapem South District, Ghana - , Joseph Kofi Baidoo; , Maxwell Kontor Owusu; , Dauglas Fofie; , Joana Anokyewaa; , Lawrence Oscar Gaisie (Archives of Current Research International, 2023)
Aim: The main aim of the study was to examine the perceptions and the determining factors of these perceptions in the implementation of inclusive education among early grade educators in the Akuapem South District of Ghana. Methodology: For this study, a descriptive survey design was employed. After reviewing extant literature, self-crafted questionnaires were validated and piloted to obtain internal consistency cronbach's alpha coefficients of 0.930 and 0.752 for perceptions of early grade educators and the factors influence the Perceptions respectively. These instruments were used to collect quantitative data from all 248 early grade educators in the district. Descriptive statistics (Means and Standard Deviations) were used to analyze data to answer both research questions. Results: The findings of the study indicated that the majority of early grade educators held the perception that inclusive education related to children with disabilities only. They lacked a comprehensive understanding of the theoretical concept of inclusive education. With respect to the factors that influenced the perceptions of early grade educators on the implementation of inclusive school practices, the study revealed that learners’ attitude, working experience with children with disabilities, availability of counsellors and counselling services and in-service training were identified. Conclusion: It is recommended that massive capacity-building programs be organized for early grade educators so as to equip them with knowledge and skills in inclusive education. Again, more Special Education coordinators and counsellors should be sent to the circuits in the district to facilitate education on inclusive education to help teachers work effectively with children with disabilities and also to promote a conducive learning environment, especially for children with disabilities.